Analysis of temperature and strain rate dependencies of softening regime for tempered martensitic steel. (May 2017) - Eisenträger, Johanna; Naumenko, Konstantin; Altenbach, Holm; Gariboldi, Elisabetta
This article aims to analyse the influence of temperature and strain rate on the mechanical behaviour of the high-chromium martensitic steel X20CrMoV12-1. The analysis is based on two series of high-temperature uniaxial tensile tests. In a first series, the tensile tests are conducted until rupture, and temperature as well as strain rate are varied systematically. The corresponding stress–strain curves show an extended softening stage. In order to examine softening, it is crucial to distinguish between microstructural changes and strain localisation due to necking. For this reason, a tensile test at low strain rate is performed several times, while the test is terminated at different strain levels in order to examine the onset of necking. Based on the test results and surface measurements of the deformed specimens, the strain level at which necking starts is determined, and possible interactions between softening and necking are discussed. The tensile tests have been conducted in order to calibrate a mechanical model which supplies reliable predictions on the material behaviour under different loading scenarios at elevated temperatures. For this reason, a framework based on microstructural processes is presented in the second part of the article. The model applies a binary mixture approach in conjunction with an iso-strain concept. Furthermore, backstress and softening variables are introduced to consider hardening and softening effects. This procedure results in a system of three differential equations describing the mechanical behaviour.